Significant progressive heterobeltiosis in banana crossbreeding - Batte, M.; Nyine, M.; Uwimana, Brigitte; Swennen, Rony L.; Akech, V.; Brown, A.; Hovmalm, H.P.; Geleta, M.; Ortíz, R. (Springer, 2020)
Background Heterobeltiosis is the phenomenon when the hybrid’s performance is superior to its best performing parent. Banana (Musa spp. AAA) breeding is a tedious, time-consuming process, taking up to two decades to develop a consumer acceptable hybrid. Exploiting heterobeltiosis in banana breeding will help to select breeding material with high complementarity, thus increasing banana breeding efficiency. The aim of this study was therefore to determine and document the level of heterobeltiosis of bunch weight and plant stature in the East African highland bananas, in order to identify potential parents that can be used to produce offspring with desired bunch weight and stature after a few crosses.